Unraveling the drought-responsive transcriptomes in nodules of two common bean genotypes during biological nitrogen fixation - da Silva, Helder Anderson Pinto; Caetano, Vanessa Santana; Pessôa, Daniella Duarte Villarinho; Pacheco, Rafael Sanches; Meneses, Carlos Henrique S. G.; Simões-Araújo, Jean Luiz (Frontiers in Plant Science, 2024)
Common bean (Phaseolus vulgaris) can efficiently fix atmospheric nitrogen when associated with Rhizobia. However, drought stress impairs plant metabolic processes, especially the biological nitrogen fixation (BNF). Here, we assessed transcriptional responses in nodules of two common bean genotypes to drought stress under BNF reliance. The RNA-Seq analysis yielded a total of 81,489,262 and 72,497,478 high quality reads for Negro Argel and BAT 477 genotypes, respectively. The reads were mapped to the Phaseolus vulgaris reference genome and expression analysis identified 145 and 1451 differentially expressed genes (DEGs) for Negro Argel and BAT 477 genotypes, respectively. Although BAT 477 had more DEGs, both genotypes shared certain drought-responsive genes, including an up-regulated heat shock protein (HSP) and a down-regulated peroxidase, indicating shared pathways activated during drought in nodule tissue. Functional analysis using MapMan software highlighted the up-regulation of genes involved in abiotic stress responses, such as HSPs and specific transcription factors (TFs), in both genotypes. There was a significant down-regulation in metabolic pathways related to antioxidant protection, hormone signaling, metabolism, and transcriptional regulation. To validate these findings, we conducted RT-qPCR experiments for ten DEGs in nodules from both genotypes, for which the expression profile was confirmed, thus reinforcing their functional relevance in the nodule responses to drought stress during BNF. BAT 477 genotype exhibited more pronounced response to drought, characterized by a high number of DEGs. The strong down-regulation of DEGs leads to transcriptional disturbances in several pathways related to stress acclimation such as hormone and antioxidant metabolism. Additionally, we identified several genes that are known to play key roles in enhancing drought tolerance, such as HSPs and crucial TFs. Our results provide new insights into the transcriptional responses in root-nodules, an underexplored tissue of plants mainly under drought conditions. This research paves the way for potential improvements in plant-bacteria interactions, contributing to common bean adaptations in the face of challenging environmental conditions.